2017
DOI: 10.1007/s10903-017-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Adherence to Preventive Dental Attendance for Preschool Children Among Filipino Immigrants in Edmonton, Alberta

Abstract: Filipino parents were open to the Western model of preventive oral healthcare, with the duration of their time in Canada playing a key role in promoting regular dental visits for their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Regarding medical insurance, the reimbursement prevalence for oral diseases is notably low in China [29], and the public must pay out of pocket for clinical treatment. The low-income population is focused on meeting basic needs and is less likely to seek dental care [30]. Furthermore, a prior study confirmed that poverty associated with education leads to reduced knowledge and a poor attitude regarding oral health [31].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding medical insurance, the reimbursement prevalence for oral diseases is notably low in China [29], and the public must pay out of pocket for clinical treatment. The low-income population is focused on meeting basic needs and is less likely to seek dental care [30]. Furthermore, a prior study confirmed that poverty associated with education leads to reduced knowledge and a poor attitude regarding oral health [31].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even where patients have access to translators they are sometimes unavailable when patients have appointments or are deemed inappropriate by patients depending on the health concern being discussed, for instance, some female patients are reluctant to discuss issues pertaining to their reproductive system using male interpreters [25]. Another key barrier is the cost of services that are not covered by the government; some families do not have extended health insurance or other financial resources to pay for medical equipment or dental care for their children [17,[26][27][28][29][30]. Many families also lack information about the range of health services and funding support for health available to them [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding medical insurance, the reimbursement rate for oral diseases is notably low in China [27], and the public must pay out of pocket for clinical treatment. The low-income population is focused on meeting basic needs and is less likely to seek dental care [28]. Furthermore, a prior study confirmed that poverty associated with education leads to reduced knowledge and a poor attitude regarding oral health [29].…”
Section: Discussionmentioning
confidence: 99%